(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
Forecasting one of the dominant parameters of fruit quality at the stage of their formation will make it possible to distribute raw materials for a waste-free chain of fruit use in advance and, subsequently, to offer variety samples for long-term storage, production of frozen products, jams, compotes, jams, and candied fruit.The widespread industrial use of fruit raw materials in the modern market implies the presence of the following characteristics of fruits in terms of varieties: high biological potential of crop productivity, resistance of fruit trees and fruits to stress and high tasting characteristics of fruits. Against the background of many factors affecting the accumulation of sugar in fruits, the influence of weather conditions is decisive. For further improvement of the technology of transportation, storage and processing of fruit raw materials, determining the share of weather indicators in the formation of the sugar fund in sweet cherry fruit is relevant. The aim of the research was to analyse the degree of influence of weather and climatic factors on the sugar content in sweet cherry fruits of three ripening periods. Sweet cherry fruits of 33 pomological varieties of early, medium and late ripening periods were selected as model varieties. Determination of the share of influence of each factor was carried out by selecting them in the study of the regression model, which was built on the basis of principal components. The statistical calculations made it possible to determine the average and strong correlation between 14 weather factors and sugar content for sweet cherry varieties of three ripening periods. The ranges of participation of weather factors that have the maximum impact on the accumulation of sugars in sweet cherry fruits from〖 ∆〗_i 9,50% to 30,99% . The weather parameters that have a predominant influence on the accumulation of sugars in cherry fruits were established: for early and middle varieties, these are the difference between the average maximum and minimum temperatures, the average maximum temperature, the amount of precipitation and the absolute minimum relative humidity during the flowering period, as well as the total number of days with precipitation in April; for late varieties, these are the absolute maximum air temperature, the difference between the average maximum and minimum temperatures, the difference between the absolute maximum and minimum temperatures during the harvesting period and the average temperature in June. The regression analysis made it possible to substantiate that the formation of the sugar fund in sweet cherry fruits of all ripening periods is most influenced by the weather conditions of the flowering period, the last month of fruit formation, as well as thermal parameters and humidity indicators at the stage of harvesting sweet cherries.